Counseling and motivational short text messages increase adherence and behavioral changes in patient with hypertension - Ginanjar Zukhruf Saputri; Akrom Akrom; Endang Darmawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background: Patients with hypertension often fail to achieve treatment goals of controlling their blood pressure, hence they fall onto the condition of uncontrolled hypertension. In addition to counseling and patient-education programme, an enhanced methods of intervention is needed by pharmacist to increase patient adherence and commitment in taking antihypertension medicine. Motivational intervention has not been widely used by pharmacist in conducting pharmaceutical care to patients. Objective: This research is aimed to understand the effect of motivational counseling and short text messages (SMS) with adherence and behavioral changes in outpatient with hypertension at PKU Muhammadiyah Hospital Bantul, Yogyakarta. Methods: Sixty patients who meet the inclusion criteria was divided into two groups, which were experimental group (n=30) who received motivational counseling and SMS, and control group (n=30) who received usual care. Data was collected by interviews, behavioral questionaire, adherence questionaire using Morisky Medication Adherence Scale (MMAS), and blood pressure measurement according to the medical record. Results: Trans theoretical model (TTM) was used in this research. Stages of behavioral changes were divided into pre-contemplation, contemplation, preparation, and action. Result showed that pharmacist intervention, using motivational counseling and SMS as reminder, contribute to an increase of patient adherence and action stage of behavioral changes in the experimental group by 50% compared to 20% in the control group (p=0,035). Increase of adherence as much as 83,33% was seen in experimental group (p=0,000). A bigger decrease of systolic and diastolic blood pressure (SBP/DBP) was also seen in the experimental group compared to control group (SBP=15,37 vs 1,27mmHg), (DBP=6,73 vs 0,43 mmHg) on their second visits. Conclusion: Based on these results, it can be concluded that motivational counseling with SMS as a reminder and motivation by pharmacists in hypertensive patients give a positive influence on behavioral changes that improve adherence, and increase of systolic and diastolic blood pressure control.